2020
DOI: 10.1016/j.ygyno.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of enhance of Zeste homolog 2 (EZH2) in endometrial carcinoma: An NRG Oncology/Gynecologic Oncology Group Study

Abstract: Objectives-Enhancer of zeste homolog 2 (EZH2) is a histone methyl transferase that mediates epigenetic silencing of tumor suppressor genes. It is commonly over-expressed in several solid tumors and has been shown to be a prognostic biomarker. We investigated patterns of EZH2 expression in endometrial cancer. Methods-Evaluation of EZH2 expression was completed on both early and advanced stage endometrioid adenocarcinoma tissues and a subset of matched normal mullerian tissue samples, from participants enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…EZH2 overexpression was first identified in prostate cancer and associated with poor clinical outcomes [ 22 ]. More researches show evidences of EZH2 overexpression in many other cancer types, including breast cancer [ 23 ], esophageal cancer [ 24 ], gastric cancer [ 25 ], anaplastic thyroid carcinoma [ 26 ], nasopharyngeal carcinoma [ 27 ], and endometrial carcinoma [ 28 ]. IHC assessment of 62 samples shows that EZH2 expression is significantly higher in BAP1-mutant renal clear cell carcinoma patients with progressed stage, grade, nodal invasion, and metastasis [ 29 ].…”
Section: Roles Of Ezh2 In Cancermentioning
confidence: 99%
“…EZH2 overexpression was first identified in prostate cancer and associated with poor clinical outcomes [ 22 ]. More researches show evidences of EZH2 overexpression in many other cancer types, including breast cancer [ 23 ], esophageal cancer [ 24 ], gastric cancer [ 25 ], anaplastic thyroid carcinoma [ 26 ], nasopharyngeal carcinoma [ 27 ], and endometrial carcinoma [ 28 ]. IHC assessment of 62 samples shows that EZH2 expression is significantly higher in BAP1-mutant renal clear cell carcinoma patients with progressed stage, grade, nodal invasion, and metastasis [ 29 ].…”
Section: Roles Of Ezh2 In Cancermentioning
confidence: 99%
“…Interestingly, EZH2 has been shown to be an oncogene and promote EnCa progression by multiple studies, which is consistent with our findings [ 33 – 35 ]. For example, EZH2 mRNA and protein expression in EnCa specimens were significantly higher than in matched-normal tissue [ 36 ]. Besides, EZH2 siRNA in combination with taxanes produced more robust anti-tumor effects versus those induced by monotherapies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of H3K27me3 did not differ between EC and normal endometrium [ 86 ]. However, Krilla et al [ 87 ] and Oki et al [ 88 ] observed that EZH2, which is responsible for H3K27me3, was overexpressed in EC compared to that in normal endometrium and is associated with poor prognosis. Dysregulation of H3K27me3 by EZH2 was found in various types of cancers [ 86 , 87 ].…”
Section: Mechanisms Of Carcinogenesis and Cancer Progression Involmentioning
confidence: 99%